2005
DOI: 10.1128/aac.49.11.4429-4436.2005
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Rifapentine and Its Primary Desacetyl Metabolite in South African Tuberculosis Patients

Abstract: This study was designed to describe the population pharmacokinetics of rifapentine (RFP) and 25-desacetyl RFP in a South African pulmonary tuberculosis patient population. Special reference was made to studying the influence of previous exposure to rifampin (RIF) and the variability in pharmacokinetic parameters between patients and between occasions and the influence of different covariates. Patients were included in the study if they had been receiving first-line antimycobacterial therapy (rifampin, isoniazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
2
10
1
Order By: Relevance
“…The high-fat meal (an English breakfast which included one fried egg) had the greatest effect (Table 3), increasing the oral bioavailability by 85.7%. This finding is consistent with previous studies (6,18). A study conducted in Hong Kong found that 2 eggs with toast increased the bioavailability of RFP to almost the same extent as a high-fat English breakfast (6).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The high-fat meal (an English breakfast which included one fried egg) had the greatest effect (Table 3), increasing the oral bioavailability by 85.7%. This finding is consistent with previous studies (6,18). A study conducted in Hong Kong found that 2 eggs with toast increased the bioavailability of RFP to almost the same extent as a high-fat English breakfast (6).…”
Section: Discussionsupporting
confidence: 83%
“…Other possible explanations include analytical interference due to food ingested 6 h after the dose, absorption windows, or progressive solubilization along the gastrointestinal tract and variable gastric emptying. Our final PK models for both RFP and 25-DRFP differ from a previously published model from our group (18). The previous model was developed to describe patient data where the participants were preinduced by rifampin and were on other antituberculosis drugs.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our clinical trial simulations suggest that dose splitting and administration of drug with high-fat food can be utilized as effective strategies to optimally achieve PK-pharmacodynamic targets, once they are firmly established. The population pharmacokinetics of single-dose RFP among patients with pulmonary TB disease have been described previously (24), and the effects of different food types on single-dose RFP exposures have also been evaluated using mathematical models (13). This analysis of single-dose and multiple-dose data from subjects receiving a broader range of RFP doses allowed exploration of the relationship between dose and bioavailability and the time and concentration dependency of clearance.…”
Section: Figmentioning
confidence: 99%
“…Moreover, the primary metabolite for RPT, 25-desacetyl rifapentine (dRPT), has also been found to be active against M. tuberculosis, although at markedly lower MICs (1,3,4). Because of these characteristics, RPT has been the subject of a number of clinical pharmacology studies aimed at evaluating pharmacokinetics and developing effective therapies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Although data from these investigations are valuable in their own right, mathematical modeling offers a way to complement these studies, synthesize their disparate data, and provide the clinician an additional tool to characterize and predict the absorption, distribution, metabolism, and excretion (ADME) of RPT under dosing conditions of interest.…”
mentioning
confidence: 99%